2013
DOI: 10.1371/journal.pone.0072451
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Niche Modeling of Bacillus anthracis on Three Continents: Evidence for Genetic-Ecological Divergence?

Abstract: We modeled the ecological niche of a globally successful Bacillus anthracis sublineage in the United States, Italy and Kazakhstan to better understand the geographic distribution of anthrax and potential associations between regional populations and ecology. Country-specific ecological-niche models were developed and reciprocally transferred to the other countries to determine if pathogen presence could be accurately predicted on novel landscapes. Native models accurately predicted endemic areas within each co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 52 publications
(106 reference statements)
3
53
0
Order By: Relevance
“…To develop models, we used 50 spatially unique anthrax outbreaks from the A1.a sublineage, as the A1.a sublineage in dominant in regions spanning from south Texas through the Dakotas (Mullins et al 2015). We expanded the outbreak dataset of Mullins et al (2013) to include new confirmed A1.a outbreaks from Texas and Colorado. Outbreaks occurred between 2000 and 2012 and included culture confirmed mortality events in livestock and wildlife.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To develop models, we used 50 spatially unique anthrax outbreaks from the A1.a sublineage, as the A1.a sublineage in dominant in regions spanning from south Texas through the Dakotas (Mullins et al 2015). We expanded the outbreak dataset of Mullins et al (2013) to include new confirmed A1.a outbreaks from Texas and Colorado. Outbreaks occurred between 2000 and 2012 and included culture confirmed mortality events in livestock and wildlife.…”
Section: Methodsmentioning
confidence: 99%
“…Outbreaks occurred between 2000 and 2012 and included culture confirmed mortality events in livestock and wildlife. We used the same environmental variables as Mullins et al (2013): elevation, annual temperature range, annual mean temperature, precipitation of the driest month, precipitation of the wettest month, annual precipitation (WorldClim database (Hijmans et al 2005)), normalized difference vegetation index (NDVI), NDVI annual amplitude and mean annual NDVI (Hay et al 2006). We also added two soils variables to improve model accuracy: average soil pH and average organic content from the harmonized world soils database (HWSD; FAO/IIASA/CISS-CAS/JRC 2008).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The environmental niche of the disease agent or vector is also needed for developing models to predict the potential geographic extent of the disease (30). This information can help inform whether a disease might affect a species throughout its geographic range or whether environmental refuges might be expected ( 31 ).…”
Section: Identifying Key Parametersmentioning
confidence: 99%
“…9 Such models provide testable hypotheses of a species' distribution potential. 10 ENM approaches have been used to predict the distribution of B. anthracis across several landscapes under current 9,[11][12][13] and future climatic conditions. 9,14 Such models provide a "first estimate" of where the pathogen may persist and Kracalik and others 7 suggested national passive surveillance should include the appropriate diagnostic tools and regional veterinary training to properly detect outbreaks in areas predicted by ENMs.…”
Section: Introductionmentioning
confidence: 99%